The reaction of consumer spending and debt to tax rebates: Evidence from consumer credit data - Annamaria Lusardi; Olivia S. Mitchell (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
We use a new panel dataset of credit card accounts to analyze how consumer responded to the 2001 Federal income tax rebates. We estimate the monthly response of credit card payments, spending, and debt, exploiting the unique, randomized timing of the rebate disbursement. We find that, on average, consumers initially saved some of the rebate, by increasing their credit card payments and thereby paying down debt. But soon afterwards their spending increased, counter to the canonical Permanent-Income model. Spending rose most for consumers who were initially most likely to be liquidity constrained, whereas debt declined most (so saving rose most) for unconstrained consumers. More generally, the results suggest that there can be important dynamics in consumers' response to 'lumpy' increases in income like tax rebates, working in part through balance sheet (liquidity) mechanisms.
urn:nbn:de:hebis:30-52350
Keywords: D91; E21; E51; E62; G2; H31; 330; Consumption; Saving; Life-Cycle Model; Permanent-Income Hypothesis; Liquidity Constraints; Fiscal Policy; Tax Cuts; Tax Rebates; Windfalls; Credit Cards; Consumer Credit; Consumer Balance Sheets; Household Finance; Verbraucherausgaben; Kreditkarte; Konsumentenverhalten; Einkommensteuer; Steuerbegünstigung; Steuerwirkung; Einkommenshypothese; USA